Costa Rica, Social Accounting Matrix, 1997 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The 1997 SAM for Costa Rica takes into account the new non-traditional export sectors spurred by the export promotion policies of the past two decades. The existing SAMs for Costa Rica do not include these new sectors and the productive linkages between these and the rest of the economy. To attend this serious gap,an effort was carried out to compile a 1997 SAM for Costa Rica, the construction of which is explained in this document along the lines of a ‘top-down’ estimation procedure. The entries of the new SAM were first adjusted in a summary set of national accounts and then subsets of estimates were adjusted to the controlling aggregate totals. The elimination of data discrepancies, in particular the reconciliation of national accounts data and survey data, was successfully implemented using the Cross-Entropy (CE) method whereby a comprehensive set of constraints could be imposed using all the prior reliable information available. The macro SAM was disaggregated to arrive at a ‘raw micro SAM’. The activity account was split into the 17 production activity accounts, including but not limited to domestic, traditional and non-traditional export agriculture, food industries, textiles, wood products, oil and chemicals, paper, construction, trade, restaurants and hotels, transport and communucation, electricity, gas and water, financial services and insurance. In consistency with the activity breakdown, the flows in the commodity account were split into 17 accounts. Row-wise these flows included intermediate consumption, private and government consumption, gross fixed capital formation, inventory change,export subsidies, and exports. Column-wise the disaggregation was for sale and consumption taxes, import tariffs, export taxes and imports, using national accounts data at the commodity level.